Graphene oxide-monohydrated manganese phosphate composites: Preparation via modified Hummers method - Yuan, Rui; Yuan, Jing; Wu, Yanping; Ju, Pengfei; Ji, Li; Li, Hongxuan; Chen, Lei; Zhou, Huidi; Chen, Jianmin (Colloids and surfaces. A, Physicochemical and engineering aspects, 2018)
[Display omitted] A modified Hummers method was established to prepare graphene oxide-MnPO4·H2O (denoted as GO-MnPO4·H2O) composites. Findings indicate that the as-formed GO-MnPO4·H2O particles are of a petal-shape and exhibit a uniform size of ∼1.2 μm, and they are stable and remain nearly unchanged after 2 day of standing at 30 ℃ in air. The formation mechanism was investigated by computer simulations in combination with experimental explorations. The Mn2+ ions obtained by oxidation reaction can be distributed around the oxygen-containing functional groups of GO (especially for hydroxyl) and interact with them via electrostatic forces or coordination bonds. The as-formed GO-Mn2+ dipolar pair can further act as the anchor sites to facilitate the growth of MnPO4·H2O. During the formation of GO-MnPO4·H2O composites, MnPO4·H2O species contributes to promoting the exfoliation of GO sheets. Moreover, the polycrystalline structure of GO-MnPO4·H2O aggregates is destroyed heavily under 450 °C, and they can be decomposed to generate reduced GO-Mn2P2O7 (denoted as rGO-Mn2P2O7) after 900 ℃ treatment in N2 atmosphere. This methodology made the synthesis of GO-MnPO4·H2O and rGO-Mn2P2O7 composites possible and may be further extended to prepare more complicated nanocomposites based on GO sheets for technological applications.